A NARRATIVE REVIEW ON MINDFULNESS-BASED INTERVENTIONS IN CANCER CARE: AN EVIDENCE-BASED APPROACH. - H. I. Farrukh, (Student's Journal of Health Research Africa, 2023)
The concept of mindfulness holds diverse interpretations, with both Eastern and Western perspectives contributing to its multifaceted nature. While mindfulness-based practices have origins in Eastern religious traditions, the Western approach emphasizes achieving mindful awareness to mitigate stress, enhance physical well-being, and foster life harmony. Historical records suggest potential advantages of mindfulness in promoting physical and mental health, particularly in cancer management. Emotions have long been associated with cancer development, dating back to classical observations linking despondency with heightened breast cancer susceptibility. This review aims to explore the utility of mindfulness in cancer management, considering diverse perspectives and historical connections. Specifically, it investigates the impact of the Mindfulness-Based Stress Reduction (MBSR) program on physical health, mental health, neuropsychological performance, and spirituality in cancer patients, focusing on bone tumors. Mindfulness-based practices have shown promise in cancer management by reducing stress, improving psychological well-being, and enhancing coping skills. Studies have revealed associations between mindfulness and beneficial outcomes, such as improved sleep quality and reduced anxiety. Mindfulness interventions have also demonstrated immunological effects and altered cytokine production. Moreover, cost-effectiveness analyses have indicated that mindfulness-based therapies can enhance quality of life at a reasonable cost. Further research is needed to explore the potential of mindfulness in reducing cancer incidence and preventing recurrence. Investigations into its immunological and psychosocial impacts, as well as its cost-effectiveness, should be expanded to provide a comprehensive understanding of its role in cancer care. Clinicians should consider incorporating mindfulness-based interventions into cancer management strategies, particularly for addressing stress, psychological distress, and improving overall well-being. However, ongoing research is essential to establish evidence-based guidelines and protocols for the effective integration of mindfulness practices in clinical settings.